Metode Diskusi dan Latihan untuk Meningkatkan Aktivitas Belajar Introduction pada Siswa Kelas VII SMPN 19 Bandar Lampung - Nurbaiti, Nurbaiti (Lentera: Jurnal Ilmiah Kependidikan, 2020)
The purpose of this study is to increase the introduction of introductory learning activities in English by applying the method of discussion and interviewing exercises with direct speakers at grade VII students of SMP Negeri 19 Bandar Lampung TP 2019/2020? The method used is classroom action research. This research was conducted on the eighth grade students of SMP Negeri 19 Bandar Lampung. The results of the research show that in the first cycle, 75.5% of the learning activity was obtained, the second cycle was 88.7% of the learning activity, the third cycle of the learning activity was 96.7% Therefore, there was an increase in activity and learning outcomes from cycle to cycle. The overall average off-task time in this learning process was 3.3%. The conclusion of this study is that the use of introductory learning (introduction) in English can be improved by applying the method of discussion and interviewing exercises with direct speakers at grade VII students of SMP Negeri 19 Bandar Lampung TP 2019/2020? "